2011
DOI: 10.1080/01904167.2011.544528
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Primula Plant in Coir Dust and Peat-Based Growing Media

Abstract: 2 This study was performed under greenhouse conditions, with coir dust, moss peat, and sedge peat as the main components of the growing media. The performance of the media was evaluated through the growth of the primula (Primula obconica) plant. In general, aeration capacities were found to be relatively low, except for growing media that included moss peat mixtures. Nevertheless, easily available water content of all growing media was found to be within the appropriate ranges. Total and water-available plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Popescu and Popescu (2015) reported that the physiological potential of petunias and ornamental tobacco is significantly influenced by the potting media in which they are grown and that the responses of the growing media to flowering varied greatly between plants. Bağcı et al (2011), Najafi et al (2019, Çiçek et al (2021) stated in their studies that coconut coir waste, peat-based hazelnut shell and husk media positively influenced quality parameters such as shoot number, total flower number, number of leaves of Primula obconica and salvia plants, and they have determined that the media with 50% hazelnut husk is the most effective media.…”
Section: Plant Growthmentioning
confidence: 99%
“…Popescu and Popescu (2015) reported that the physiological potential of petunias and ornamental tobacco is significantly influenced by the potting media in which they are grown and that the responses of the growing media to flowering varied greatly between plants. Bağcı et al (2011), Najafi et al (2019, Çiçek et al (2021) stated in their studies that coconut coir waste, peat-based hazelnut shell and husk media positively influenced quality parameters such as shoot number, total flower number, number of leaves of Primula obconica and salvia plants, and they have determined that the media with 50% hazelnut husk is the most effective media.…”
Section: Plant Growthmentioning
confidence: 99%
“…The effective utilization of agroforestry waste is vital for resource development, environmental protection, ecological nutrient cycling, and sustainable resource development. Studies have demonstrated that agroforestry waste like corn stover, coconut husk, and sawdust can be used successfully instead of peat in the cultivation of geranium, calendula, garlic, and primula [10][11][12]. Some studies have shown that rotting leaf mold and rice husks can replace peat as a plant growth medium, where they not only help with adequate nutrients but also have better water retention and air permeability and offer lightweight substrates that reduce transportation costs and yield greater economic advantages [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Cocopeat is widely used for containerized growing medium for the production of ornamental potter plants (Bagci et al, 2011;Scagel, 2003;Tariq et al, 2012) and other horticultural species (Ayesha et al, 2011;Erwan et al, 2013;Rubio et al, 2011;Tehranifar et al, 2007). Cocopeat is a suitable growing media with acceptable physical and chemical attributes such as pH, electrical conductivity, bulk density and others (Abad et al, 2002).…”
Section: Introductionmentioning
confidence: 99%